Morrison's Use of Symbolism: The Significance of Blue Eyes in The Bluest Eye - Muahamad, Hajar Hassan; Salh, Pana Mahmud; Mahmud, Shene Jamal; Ahmad, Hedayat Muhamad; Abdlalla, Shabaz (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
The symbolic and psychological meaning of blue eyes in Toni Morrison's The Bluest Eye is critically examined in this analysis with a specific emphasis on the destructive effect of Eurocentric definitions of beauty on Black identity and self-esteem. Through the tragic Pecola Breedlove, Morrison lays bare how cultural definitions of beauty specifically the idealization of Whiteness and blue eyes result in internalized racism, self-loathing, and mental breakdown among African Americans. The study examines how these ideals are sustained in literature, the media, domestic life, and text materials to create a cultural discourse whereby Blackness is belittled. Blue eyes are used by Morrison not just as physical appearance but as Whiteness, acceptance, and worth attributes denied Blacks in the segregated world. By analyzing Symbolism, form, and periodization in the novel, this volume argues that The Bluest Eye is both a caustic critique of racialized codes of beauty and an imperative to rewrite cultural values on terms friendly to Black dignity, worth, and personhood.